2011
DOI: 10.1111/j.2044-8260.2010.02005.x
|View full text |Cite
|
Sign up to set email alerts
|

The British Journal of (Social and) Clinical Psychology- a brief citation review

Abstract: Editorial The British Journal of (Social and) Clinical Psychology -a brief citation reviewThis editorial marks the 50th volume of the, now, British Journal of Clinical Psychology, whose first nineteen volumes formed part of a combined British Journal of Social and Clinical Psychology. A hallmark of the journal has always been its capture of the generic scope of academic clinical psychology nationally and internationally with a firm commitment to the use of robust scientific methodologies. For the purposes of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…By 1980, social and clinical psychology in Britain had grown in strength and the original BJSCP separated into two journals ( BJCP and BJSP ) in 1981. A review of the first 50 volumes of the BJCP , including 13 volumes of BJSCP , by the former editors (Barkham et al, 2011) identified 13 highly cited articles; the most cited was authored by Wing (1962) on the impact of institutionalisation on the mental health of patients. This reflected the substantial debate about care and treatment of people with mental health problems which erupted in the 1960s.…”
Section: Back To Recession 1970s–1980smentioning
confidence: 99%
See 1 more Smart Citation
“…By 1980, social and clinical psychology in Britain had grown in strength and the original BJSCP separated into two journals ( BJCP and BJSP ) in 1981. A review of the first 50 volumes of the BJCP , including 13 volumes of BJSCP , by the former editors (Barkham et al, 2011) identified 13 highly cited articles; the most cited was authored by Wing (1962) on the impact of institutionalisation on the mental health of patients. This reflected the substantial debate about care and treatment of people with mental health problems which erupted in the 1960s.…”
Section: Back To Recession 1970s–1980smentioning
confidence: 99%
“…The second theme they noted was the impact of cognitive psychology on research into mental illness. However, the editors noted that ‘a dominant feature of the listed articles relates to measures and measurement’ with Hamilton’s measure of depression being described as a ‘super citation’ (Barkham et al, 2011: 4) accounting for 8.8 per cent of Web of Science citation counts for the BJSCP between 2006 and 2010. They compared this high rate of citation of measurement articles with comparable American journals and found a similar high rate, thus confirming the importance of measurement within clinical psychology research.…”
Section: Back To Recession 1970s–1980smentioning
confidence: 99%
“…An appropriate analytic tool is the Rasch measurement model [29]. This model provides strict post-hoc tests of unidimensionality [30] and it is widely used in the development of mental health scales [31]. Moreover, the Rasch model informs the applicability of scales across different populations (item bias) and provides a hierarchy of scale items [32].…”
Section: Introductionmentioning
confidence: 99%